Assessment of changes in atmospheric dynamics and dust activity over southwest Asia using the Caspian Sea–Hindu Kush Index. (30th March 2017) - Kaskaoutis, D. G.; Rashki, A.; Houssos, E. E.; Legrand, M.; Francois, P.; Bartzokas, A.; Kambezidis, H. D.; Dumka, U. C.; Goto, D.; Takemura, T.
ABSTRACT: This study examines the influence of the Caspian Sea–Hindu Kush Index (CasHKI) on local and synoptic meteorology as well as on dust emissions over southwest (SW) Asia by means of National Center for Environmental Prediction/National Center for Atmospheric Research (NCEP‐NCAR) re‐analysed mean sea‐level pressure (MSLP), geopotential height at 700 hPa and surface meridional wind, along with meteorological data at Zabol, east Iran and Meteosat/Infrared Difference Dust Index (IDDI) retrievals. The analysis focuses on the summer period (June to September) of 2000–2014 and the winter period (November to March) of 1963–2014. The CasHKI values are mostly controlled by the MSLP anomalies over the Caspian Sea (CS) domain, varying from approximately −25 to +35 hPa in winter and from approximately−10 to +14 hPa in summer, but without a clear annual pattern. The CasHKI values are classified into four modes for each month depending on their intensity. In the summer months, the high CasHKI mode is associated with enhanced MSLP over central Asia and deepening of the Indo‐Pakistan thermal low associated with the Indian summer monsoon. At 700‐hPa level, the high CasHKI mode shows an enhancement of the Arabian ridge, expanding it to the north over Iran and the CS, with a concurrent strengthening of the Indian trough, leading to intensification of northerly winds along east Iran. This results in significant increase in dust activity over SW Asia, which is also apparent in the winter months. Furthermore, the intensification of the northerly flow associated with the high CasHKI modes drops the temperature and increases the relative humidity over Zabol, especially during winter. The SPRINTARS‐model simulations also show increased dust emissions and concentrations for the high CasHKI values, confirming that the CasHKI variations modulate the dust activity over SW Asia throughout the year.